Image Water Marking Using Cryptography - Dheeraj Sai, DVLN; KNS, Aneesh (International Journal of Computer Sciences and Engineering, 2025)
A digital watermark is a kind of marker convertly embedded in a noise tolerant signal such as audio or image data. It is typically used to identify ownership of the copyright of such signal. Watermarking is a process of hiding digital information in a carrier signal, the hidden information should but doesnot need to contain a relation to the carrier signal. Digital watermarks may be used to verify the authenticity or integrity of the carrier signal or to show the identity of its owners. It is prominently used for tracing copyright infringements and for bank note authentication. Traditional watermarks may be applied to visible media such as images or video, whereas in digital watermarking, the signal may be audio, pictures, video, texts or 3D models. A signal may carry several different watermarks at the same time.